THE EFFECT OF PERCEIVED PRODUCT QUALITY, BRAND IMAGE, AND PROMOTION ON CUSTOMER PURCHASE INTENTION (CASE OF ZARA CUSTOMERS IN GRAND INDONESIA, JAKARTA) - Yonathan Delvonvio Kent; Innocentius Bernarto (Indonesian Marketing Journal, 2021)
The purpose of this study was to test whether the perception of product quality, brand image, and promotion had a positive effect on consumer buying interest. The survey method was applied to obtain data through a questionnaire. The research population target is all ZARA customers in Grand Indonesia, Jakarta. The sampling technique was done by purposive sampling. The number of samples is 400 respondents. Data analysis using SmartPLS program with partial least square-structural equation modeling (PLS-SEM) approach. The results showed that the perception of product quality, brand image, and promotion had a positive effect on the buying interest of ZARA consumers in Grand Indonesia Jakarta.BAHASA INDONESIA ABSTRACTTujuan penelitian ini adalah untuk menguji apakah persepsi kualitas produk, citra merek, dan promosi berpengaruh positif terhadap minat beli konsumen. Metode survey diaplikasikan untuk mendapatkan data melalui kuesioner. Target populasi penelitian adalah seluruh pelanggan ZARA di Grand Indonesia, Jakarta. Teknik pengambilan sampel dilakukan dengan purposive sampling. Jumlah sampel sebesar 400 responden. Analisis data menggunakan program SmartPLS dengan pendekatan partial least square-structural equation modelling (PLS-SEM). Hasil penelitian menunjukkan bahwa persepsi kualitas produk, citra merek, dan promosi berpengaruh positif terhadap minat beli konsumen ZARA di Grand Indonesia Jakarta.